2013
DOI: 10.1002/jcp.24294
|View full text |Cite
|
Sign up to set email alerts
|

Unraveling amyloid toxicity pathway in NIH3T3 cells by a combined proteomic and1H‐NMR metabonomic approach

Abstract: A range of debilitating human diseases is known to be associated with the formation of stable highly organized protein aggregates known as amyloid fibrils. The early prefibrillar aggregates behave as cytotoxic agents and their toxicity appears to result from an intrinsic ability to impair fundamental cellular processes by interacting with cellular membranes, causing oxidative stress and increase in free Ca(2+) that lead to apoptotic or necrotic cell death. However, specific signaling pathways that underlie amy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
14
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 10 publications
(16 citation statements)
references
References 72 publications
2
14
0
Order By: Relevance
“…As expected, in the absence of D-ribose, early prefibrillar aggregates (0 and 5 days) strongly affected cell viability (about 40% MTT reduction), whereas fibrillar aggregates (10 days) did not ( Figure 8 ) in accordance with previous studies [20], [22]. Conversely, aggregates formed in the presence of D-ribose after 5 days of incubation did not affect cell viability supporting our finding that D-ribose induces rapid formation of harmless fibrillar aggregates.…”
Section: Resultssupporting
confidence: 92%
See 1 more Smart Citation
“…As expected, in the absence of D-ribose, early prefibrillar aggregates (0 and 5 days) strongly affected cell viability (about 40% MTT reduction), whereas fibrillar aggregates (10 days) did not ( Figure 8 ) in accordance with previous studies [20], [22]. Conversely, aggregates formed in the presence of D-ribose after 5 days of incubation did not affect cell viability supporting our finding that D-ribose induces rapid formation of harmless fibrillar aggregates.…”
Section: Resultssupporting
confidence: 92%
“…In particular, the replacement of both indole residues located at positions 7 and 14 in the N-terminal region with phenylalanine (W7FW14F) renders myoglobin highly susceptible to aggregation and able to form amyloid fibrils under physiological conditions of pH and temperature [16][19]. Similarly to other amyloidogenic proteins, the cytotoxicity of the W7FW14F apomyoglobin aggregates is associated to the early oligomers intermediates rather than mature fibrils [20][22]. These features make the W7FW14F myoglobin a suitable model for studying the molecular mechanisms underlying amyloid aggregation under physiological conditions.…”
Section: Introductionmentioning
confidence: 99%
“…We demonstrated that the cytotoxicity induced by W7FW14F ApoMb is closely related to oxidative stress [Sirangelo et al, ; Vilasi et al, ]. Similarly to previous studies aimed at evaluating the mechanisms of amyloid‐β‐induced neurotoxicity [Bate et al, ; Li et al, ], our data show that the time‐dependent decrease of cell viability elicited by W7FW14F ApoMb insult is prevented by PAF‐R antagonist, CV3988, thus suggesting the involvement of PAF signaling in the apoptotic pathway activated by W7FW14F ApoMb.…”
Section: Discussionsupporting
confidence: 84%
“…We first evaluated the oxidative stress induced by W7FW14F ApoMb amyloid oligomers, known to occur at early time of cell exposure to aggregates [Sirangelo et al, ; Vilasi et al, ]. Results indicated that exposure of SH‐SY5Y cells to W7FW14F ApoMb aggregates up to 360 min led to a significant increase of intracellular ROS compared with untreated cells ( P < 0.05 at 15, 30, and 60 min, P < 0.01 at 180 and 360 min) (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation